THE STRUCTURAL DIVERSITY OF ART DECO IN MODERN EUROPEAN CERAMICS - Ibrahim Qassem Mutlab Dagher; Assad jawadabudmoslem (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
The purpose of this paper isto know the structural diversity of Art Deco in modern ceramics,The limits of the research were limited to the study of German ceramic formations between (1920-1945),The research procedures included (18) works by European potters, and the research sample was represented by (3) ceramic works, these models were selected in an intentional way, as the analysis of the sample models was based on the descriptive (analytical) approach. The most important result of the researchers that the colors applied to the ceramic shapes gave a new rhythm that helped diversify the structure of the ceramic composition; Structural diversity is achieved in the art of modern European ceramics according to the effectiveness of the visual construction (form and content) of the ceramic formations. In addition, they are the conclusions the technical aspect took an important role in showing the symbolic semantic dimension as well as verification of diversity in the European ceramic composition with the currents of modernity at the level of form.